👤

a)[tex] \frac{3x-5}{7} [/tex]+[tex] \frac{x+4}{2} [/tex]=[tex] \frac{5x-7}{14} [/tex]+[tex] \frac{x}{2} [/tex]
b)[tex] \frac{3x}{10}-[tex] \frac{x+1}{5} [/tex]=[tex] \frac{x+3}{2} [/tex]+[tex] \frac{2x+3}{5} [/tex]-[tex] \frac{11}{10} [/tex]
c)[tex] \frac{2(3x+1)}{15} [/tex]+[tex] \frac{x+5}{3} [/tex]=[tex] \frac{3x-2}{5} [/tex]-[tex] \frac{3(x+1)}{15} [/tex][tex] \frac{2}{5} [/tex]
d)[tex] \frac{6x-5}{12} - \frac{3x+1}{6}= \frac{4x-3}{3} - \frac{5x+1}{4} [/tex]


Răspuns :

+=+
(6x-10+7x+28)/14=(5x-7+14x)/14             ·14
13x+18=19x-7
13x-19x=-7-18
-6x=-25              (-1)
x=25/6=4,1(6)

c)+=-
6x+2+5x+25=9x-6-3x-3   ?2/5
d)
6x-5-6x-2=16x-12-15x-3
-7=x-15
-x=-15+7
-x=-8   (-1)
x=8